1989
DOI: 10.1126/science.2492678
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Interleukin-2 Signaling: Mediation of Different Outcomes by a Single Receptor and Transduction Pathway

Abstract: The T cell lymphokine, interleukin-2 (IL-2), plays a pivotal role in an immune response by stimulating antigen-activated B lymphocytes to progress through the cell cycle and to differentiate into antibody-secreting cells. An IL-2 inducible B lymphoma line, in which the growth and differentiation responses are uncoupled, provides a model system for dissecting the signaling mechanisms operating in each response. This system was used to show that both signals are initiated by IL-2 binding to a single, unifunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
43
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(48 citation statements)
references
References 50 publications
4
43
1
Order By: Relevance
“…Interleukin-2 (IL-2) is aT cell-derived cytokine involved in the proliferation and differentiation of T lymphocytes, B lymphocytes, NK cells as well as monocytes [1][2][3][4]. Upon antigen recognition by T lymphocytes, the induction of both IL-2 and IL-2R gene expression allows subsequent proliferation of activated clones, either in an autocrine or paracrine fashion [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-2 (IL-2) is aT cell-derived cytokine involved in the proliferation and differentiation of T lymphocytes, B lymphocytes, NK cells as well as monocytes [1][2][3][4]. Upon antigen recognition by T lymphocytes, the induction of both IL-2 and IL-2R gene expression allows subsequent proliferation of activated clones, either in an autocrine or paracrine fashion [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…The p55 chain binds IL-2 with a low affinity (Kd ti10 -g M), the p70-75 chain binds IL-2 with an intermediate affinity (Kd N10'9 M), and both molecules form a noncovalently linked heterodimer that binds IL-2 with high affinity (Kd _10 -12 M) . The response of T or B cells to IL-2 seems to be mediated by p70-75 and not p55 (5,6) . Human monocytes respond to IL-2 with induction of IL-1 mRNA (7), development oftumoricidal activity (2), and we have recently shown that IL-2 enhances c-fms mRNA expression (Espinoza-Delgado et al, manuscript submitted).…”
mentioning
confidence: 99%
“…Because it is reported that IL-4 does not induce Ca2+ mobilization or protein kinase C activation (28), IL-4 and PMA inhibit IL-5-mediated BCL1-B20 cell differentiation in a different intracellular mechanism. Consequently, it would be interesting to use IL-4 and PMA as inhibitors for IL-5-induced IgM secretion and IL-5-induced signaling.…”
Section: Discussionmentioning
confidence: 99%